Short-term rewetting after summer drought does not alter soil fungal community composition and manganese peroxidase activity in managed temperate beech forests - Shanza Zaib; Michaela Caboňová; Slavomír Adamčík; Marcel Zámocký; Jana Harichová; Zuzana Gajdošová; Katarína Adamčíková; Milan Valachovič; Richard Hrivnák; Tomáš Větrovský; Markus Gorfer; Rebecca Horváthová; et al. (PLoS ONE, 2026)
Climate change is increasing the frequency of drought–rewetting cycles in temperate forests, yet the short-term responses of soil fungal communities to these events remain poorly resolved. We investigated whether an intense summer drought followed by heavy rainfall alters fungal community composition and oxidative enzyme activity in managed temperate beech forests of Central Slovakia. Soil samples from litter and mineral horizons were collected before and seven days after a rainfall event that followed an 18-day dry period. Fungal communities were characterized using ITS2 metabarcoding, and manganese peroxidase (MnPox) activity was measured as an indicator of oxidative decomposition potential. Fungal communities differed strongly between litter and mineral soil horizons across taxonomic and trophic classifications. Ectomycorrhizal fungi and soil saprotrophs dominated the mineral soil, whereas plant pathogens, litter saprotrophs, and wood-decomposing fungi were more abundant in the litter layer. In contrast, short-term rewetting did not produce detectable changes in fungal community composition or alpha diversity within either horizon. MnPox activity showed substantial spatial variability among plots but no consistent response to the rainfall event. Together, these results indicate that vertical stratification exerts a stronger influence on fungal community structure than short-term moisture fluctuations in these beech forest soils. The absence of rapid compositional change suggests that fungal communities in mature temperate forests may exhibit short-term resistance to drought–rewetting pulses, highlighting the importance of soil structure and litter layers in buffering microbial communities against transient climatic extremes.